Avaliação da fosforilação da AKT e do conteúdo da proteína transportadora de glicose GLUT4 em músculo esquelético de ratos adultos com lesão periapical - Pereira, Renato Felipe [UNESP] (2014)
Currently, there is some consensus in the dental area related to the fact that chronic inflammation in teeth may eventually lead to systemic disorders. Periapical lesion (PL) is characterized as an oral inflammation and it is associated to the increase of proinflammatory citokines, such as IL-6 and TNF-alpha, that can possibly induce insulin resistance. Insulin resistance can be defined as the state in which there is a glucose uptake decrease by tissue in response to insulin stimulation, however, the mechanisms that cause insulin resistance are not totally understood. Former studies from our laboratory demonstrated that adult rats with periapical lesion showed changes in the initial stage of insulin signaling and lower insulin sensitivity. Based on that, more studies are needed in order to verify whether these changes are also present in the continuity of the insulin signaling cascade and glucose transporter protein 4 (GLUT4) expression. The aims of this study were to evaluate in rats with PL: 1) plasma glucose and insulin levels (n=10); 2) insulin sensitivity by the HOMA-IR index (n=10); 3) serine/ threonine phosphorylation status of Akt in skeletal muscle gastrocnemius (GM) (n=6); 4) content of GLUT4 protein and its translocation index for plasma membrane in GM (n=5). Therefore, 32 Wistar rats (2 months old) were used and divided into two groups: a) control rats without PL b) rats with PL induced in right upper molars by using a carbon steel drill fitted with ball 0.1 mm. From the results it was observed that rats with PL showed: 1) no difference in blood glucose and insulin; 2) decrease in insulin sensitivity assessed...